Mitragyna speciosa Leaf Extract Exhibits Antipsychotic-Like Effect with the Potential to Alleviate Positive and Negative Symptoms of Psychosis in Mice - Vijeepallam, Kamini; Pandy, Vijayapandi; Kunasegaran, Thubasni; Murugan, Dharmani D.; Naidu, Murali (Frontiers in Pharmacology, 2016)
In this study, we investigated the antipsychotic-like effect of methanolic extract of Mitragyna speciosa leaf (MMS) using in vivo and ex vivo studies. In vivo studies comprised of apomorphine-induced climbing behaviour, haloperidol-induced catalepsy, and ketamine-induced social withdrawal tests in mice whereas the ex vivo study was conducted utilizing isolated rat vas deferens preparation. Acute oral administration of MMS (50-500 mg/kg) showed an inverted bell-shaped dose-response in apomorphine-induced cage climbing behaviour in mice. The effective inhibitory doses of MMS (75 and 100 mg/kg, p.o.) obtained from the apomorphine study was further tested on haloperidol (subcataleptic dose; 0.1 mg/kg, i.p.)-induced catalepsy in the mouse bar test. MMS (75 and 100 mg/kg, p.o) significantly potentiated the haloperidol-induced catalepsy in mice. Interestingly, MMS at the same effective doses (75 and 100 mg/kg, p.o) significantly facilitated the social interaction in ketamine-induced social withdrawal mice. Furthermore, MMS inhibited the dopamine-induced contractile response dose-dependently in the isolated rat vas deferens preparations. In conclusion, this investigation provides first evidence that MMS exhibits antipsychotic-like activity with potential to alleviate positive as well as negative symptoms of psychosis in mice. This study also suggests the antidopaminergic activity of MMS that could be responsible for alleviating positive symptoms of psychosis.